2016
DOI: 10.1097/cji.0000000000000125
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Affibody-Auristatin E Conjugate With a Potent and Selective Activity Against HER2+ Cell Lines

Abstract: Targeted therapy is a new type of cancer treatment that most often uses biologically active drugs attached to a monoclonal antibody. This so called antibody-drug conjugate strategy allows the use of highly toxic substances that target tumor cells specifically, leaving healthy tissues largely unaffected. Over the last few years, antibody-drug conjugates have become a powerful tool in cancer treatment. We developed and characterized a novel cytotoxic conjugate against HER2 tumors in which the antibody has been s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 51 publications
1
42
0
Order By: Relevance
“…The fluorescently labeled anti-HER2 diaffibody was used to stain the SK-BR-3 cells, which strongly overexpress HER2, and the control U-87 MG cells, which have physiological levels of HER2. The HER2 status of these cell lines was previously confirmed by SDS-PAGE analysis [41]. A similar experiment was also performed with commercially available anti-HER2 mouse monoclonal antibodies, followed by donkey anti-mouse polyclonal antibodies conjugated with FITC.…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…The fluorescently labeled anti-HER2 diaffibody was used to stain the SK-BR-3 cells, which strongly overexpress HER2, and the control U-87 MG cells, which have physiological levels of HER2. The HER2 status of these cell lines was previously confirmed by SDS-PAGE analysis [41]. A similar experiment was also performed with commercially available anti-HER2 mouse monoclonal antibodies, followed by donkey anti-mouse polyclonal antibodies conjugated with FITC.…”
Section: Resultsmentioning
confidence: 91%
“…Importantly, we previously reported that all these cell lines are similarly sensitive to free MMAE [41,51]. The cytotoxicity of (Z HER2:4 ) 2 DCS-MMAE was measured by the MTT proliferation assay (Figure 9 and Figure 10).…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations